Analisis Pengelolaan Ruang Terbuka Hijau di Tiga Taman di Kota Kupang (Studi Kasus Taman Nostalgia, Taman Ina Bo’i dan Taman Tirosa) - Destina Koroh; Mamie E. Pellondo’u; Astin E. Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
The purpose of this research is to know the role of government in the management of green open space in three city parks, knowing the implementation of Green Open Space governance in Three City Parks, knowing the benefits of green open space in three City Parks (Nostalgia Park, Ina Bo'I and Tirosa Park). This research was carried out in Nostalgia Park, Ina Bo'I Park and Tirosa Park from October to November 2021 with a total of 384 respondents Data collection techniques used in this study are interviews, questionnaires, documents and archives. From the data collected, a descriptive qualitative data analysis was carried out. The results of this study indicate that the management of green open spaces in three city parks by the Kupang City Environment and Hygiene Service describes four aspects, namely planning, organization, implementation and supervision. The implementation of Green Open Space governance in the three city parks has several conceptual elaborations, namely, the location of the city park is adjusted to the direction of the RTRWK (City Spatial Planning) and still pays attention to the city parks that already exist today. The activities developed are a combination of ecological interests, family tourism and limited sports. The types of plants developed are prioritized on typical/local plants and plants that have aesthetic value and shade plants. In terms of the benefits of green open space for visitors, 24% of the community can gather with friends and family, 21% enjoy the scenery and refreshment, 15% reduce stress from work, 14% can get fresh air and can exercise and 12% enjoy the garden atmosphere.